2007
DOI: 10.1093/ecam/nem087
|View full text |Cite
|
Sign up to set email alerts
|

Iyengar Yoga Increases Cardiac Parasympathetic Nervous Modulation among Healthy Yoga Practitioners

Abstract: Relaxation techniques are established in managing of cardiac patients during rehabilitation aiming to reduce future adverse cardiac events. It has been hypothesized that relaxation-training programs may significantly improve cardiac autonomic nervous tone. However, this has not been proven for all available relaxation techniques. We tested this assumption by investigating cardiac vagal modulation during yoga.We examined 11 healthy yoga practitioners (7 women and 4 men, mean age: 43 ± 11; range: 26–58 years). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(105 citation statements)
references
References 18 publications
10
87
1
2
Order By: Relevance
“…The significant increase of post exercise value of mean R-R interval, SDNN, RMSSD was observed in this study which is consistent with findings of other researchers in healthy subjects after practicing yoga 23,24 . But some researchers reported about no significant change after breathing exercise in both healthy subjects and diseased condition 12,15,19,25 .…”
Section: Discussionsupporting
confidence: 93%
“…The significant increase of post exercise value of mean R-R interval, SDNN, RMSSD was observed in this study which is consistent with findings of other researchers in healthy subjects after practicing yoga 23,24 . But some researchers reported about no significant change after breathing exercise in both healthy subjects and diseased condition 12,15,19,25 .…”
Section: Discussionsupporting
confidence: 93%
“…The study with the longest follow-up length (30) stands out with ten years. Yoga is a combination of physical exercise, breathing techniques and meditation that positively influences the autonomous cardiac system (42) . Yoga programs enable improvement in symptom perception, higher muscle strength and exercise tolerance, in addition to balance.…”
Section: Discussionmentioning
confidence: 99%
“…Although not completely understood, yoga effects changes in the parasympathetic nervous system, positively affecting heart rate variability. 86 Fourteen controlled studies 27 -32, 87 -94 and 4 systematic reviews 95 -98 were identified, and all uncontrolled trials and those in which yoga was not the sole treatment intervention 99 were eliminated from consideration. The conclusions of the systematic reviews can be summarized as follows: yoga appears to be a promising complementary therapy for children and adolescents, especially for those with pain and emotional, mental, and behavioral conditions, with very few reported adverse effects.…”
Section: Yogamentioning
confidence: 99%